Keberhasilan inseminasi buatan menggunakan semen beku dan semen cair pada sapi Peranakan Ongole - Trinil Susilawati; Nurul Isnaini; Aulia Puspita Anugra Yekti; Ika Nurjannah; Errico Errico; Nolasco da costa (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The purpose of this research was to know about the successfully artificial insemination (AI) using frozen and liquid semen of Ongole cross (PO) cattle indicated by Service per Conception (S/C), Days Open (DO) dan Conception Rate (CR). The materials used were 60 heads of Ongole crossbred cattle which were selected purposively using some criteria, such as having calving experience, healthy, and free from any reproduction disorder. This field experiment consisted of direct observation and interview to acquire primary and secondary data. Datas were analyzed descriptively and continued by a paired t-test. The results showed that the value of (S/C) was very significantly different (P<0.01),  DO was not significantly different (P>0.05). CR for P1, P2, P3, and P4 was found 63.33% , 86.67%, 16.33%, 83.33% respectively. The conclusion of this research was AI using frozen and liquid semen with only 5 days preservation had a difference on the value of service per conception. The most successfull AI was found higher in the liquid semen which was stored for 1 and 5 days than that of frozen semen. Key words : semen, service per conception, days open, calving interval